2021
DOI: 10.21775/cimb.041.221
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Incoming HSV-1 Genomes Entering the Nucleus

Abstract: Herpesvirus genomes enter the eukaryotic nucleus as large linear double stranded DNA molecules that are free of any proteins (naked DNA). Once inside the nucleus, the HSV-1 genomes immediately associate with proteins that will be instrumental in the organization and regulation of these genomes.These initial interactions are thought to determine the fate of the infecting genomes. In general, the host cell has evolved several mechanisms to suppress viral genomes and induce latent or abortive infections. On the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…Several studies suggested that HSV-1 genomes injected into the nucleus of IFN pre-treated cells cannot initiate transcription (65,66). This restriction is exacerbated in HSV-1 mutants lacking the viral E3 RING ubiquitin ligase ICP0 (54,(67)(68)(69). We previously reported that treatment with IFN-β reversibly silenced MCMV infection in endothelial and fibroblast cells (56).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that HSV-1 genomes injected into the nucleus of IFN pre-treated cells cannot initiate transcription (65,66). This restriction is exacerbated in HSV-1 mutants lacking the viral E3 RING ubiquitin ligase ICP0 (54,(67)(68)(69). We previously reported that treatment with IFN-β reversibly silenced MCMV infection in endothelial and fibroblast cells (56).…”
Section: Discussionmentioning
confidence: 99%
“…During latency, viral transcription is severely restricted, there is no significant expression of any viral proteins, or viral DNA replication, and no infectious virions are produced. The mechanisms that result in the silencing of the viral genomes are likely multifactorial and remain incompletely characterized, but there is a general consensus in that chromatin epigenetics play a major role ( Bloom et al, 2010 ; Cliffe and Wilson, 2017 ; Knipe and Cliffe, 2008 ; Lieberman, 2016 ; Nicoll et al, 2012 ; Singh and Tscharke, 2020 ; Washington et al, 2019 ); recently reviewed in ( Kobiler and Afriat, 2021 ).…”
Section: Hsv-1 2 Lytic and Latent Cyclesmentioning
confidence: 99%
“…Briefly summarizing, histone PTM associated with transcription ( e.g., H3 K9ac, K14ac, K4me3) have been consistently reported to associate with transcribed HSV-1 genes during lytic infections and histone PTM normally associated with silencing ( e.g., H3K9me2/3 or K27me3), with genes transcribed to only low levels or not at all ( Fig. 7 ) (recently reviewed in Kobiler and Afriat, 2021 ). VP16 recruits to the IE promoters the HDM LSD1/KDM1A to remove H3K9me3, which is associated with silencing.…”
Section: The Hsv-1 Epigenomementioning
confidence: 99%
See 2 more Smart Citations